Altitudinal migration: ecological drivers, knowledge gaps, and conservation implications - Hsiung, An C.; Boyle, W. Alice; Cooper, Robert J.; Chandler, Richard B. (Biological reviews of the Cambridge Philosophical Society, 2018)
ABSTRACT Animal migration has been the subject of intensive research for more than a century, but most research has focused on long‐distance rather than short‐distance migration. Altitudinal migration is a form of short‐distance migration in which individuals perform seasonal elevational movements. Despite its geographic and taxonomic ubiquity, there is relatively little information about the intrinsic and extrinsic factors that influence altitudinal migratory behaviour. Without this information, it is difficult to predict how rapid environmental changes will affect population viability of altitudinal migrants. To synthesize current knowledge, we compiled literature on altitudinal migration for all studied taxa, and identified the leading hypotheses explaining this behaviour. Studies of animal altitudinal migration cover many taxonomic lineages, with birds being the most commonly studied group. Altitudinal migration occurs in all continents except for Antarctica, but about a third of the literature focused on altitudinal migration in North America. Most research suggests that food and weather are the primary extrinsic drivers of altitudinal migration. In addition, substantial individual‐level variation in migratory propensity exists. Individual characteristics that are associated with sex, dominance rank, and body size explain much of the variation in migratory propensity in partially migratory populations, but individual‐level correlates are poorly known for most taxa. More research is needed to quantify the effects of habitat loss, habitat fragmentation, and climate change on altitudinal migrants. Demographic studies of individually marked populations would be particularly valuable for advancing knowledge of the cascading effects of environmental change on migratory propensity, movement patterns, and population viability. We conclude our review with recommendations for study designs and modelling approaches that could be used to narrow existing knowledge gaps, which currently hinder effective conservation of altitudinal migratory species.